Whole Genome Sequencing: Applications in Clinical Bacteriology - Mustafa, Abu Salim (Medical principles and practice, 2024)
Abstract The success in determining the whole genome sequence of a bacterial pathogen was first achieved in 1995 by determining the complete nucleotide sequence of Haemophilus influenzae Rd using the chain-termination method established by Sanger et al. in 1977 and automated by Hood et al. in 1987. However, this technology was laborious, costly, and time-consuming. Since 2004, high-throughput next-generation sequencing technologies have been developed, which are highly efficient, require less time, and are cost-effective for whole genome sequencing (WGS) of all organisms, including bacterial pathogens. In recent years, the data obtained using WGS technologies coupled with bioinformatics analyses of the sequenced genomes have been projected to revolutionize clinical bacteriology. WGS technologies have been used in the identification of bacterial species, strains, and genotypes from cultured organisms and directly from clinical specimens. WGS has also helped in determining resistance to antibiotics by the detection of antimicrobial resistance genes and point mutations. Furthermore, WGS data have helped in the epidemiological tracking and surveillance of pathogenic bacteria in healthcare settings as well as in communities. This review focuses on the applications of WGS in clinical bacteriology. Highlights of the StudyWhole genome sequencing has been projected to revolutionize the practice of clinical bacteriology due to increased efficiency and reduced time and cost.Whole genome sequencing can be used to identify bacterial species and genotypes from cultures and clinical specimens.Whole genome sequencing can also help in the detection of antimicrobial resistance mechanisms and epidemiologic tracking and surveillance of pathogenic bacteria.